2016
DOI: 10.1680/jgele.16.00103
|View full text |Cite
|
Sign up to set email alerts
|

Coarse granular flow interaction with slit structures

Abstract: Coarse grains accumulate in geophysical flow fronts and have high solid fractions. Such fronts may arch in slit structures such as baffles and slit dams, leading to the rapid trapping of particles and potentially high-energy overflow. Existing empirical slit-structure design recommendations are limited and inadequate since they only focus on the slit size to particle diameter ratio (s/δ) and neglect the pileup height and pre-impact flow energy. Flume modelling was thus adopted to study coarse flow fronts impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…For clumps, the grain diameter is calculated as the equivalent diameter of a sphere with the same volume as the clump 5, it is worth noting that as b/d max increases from 3 to 7; more granular materials can pass through the slits. The evolutions of granular flow run up, pile up, and dead zone formation have also been observed in laboratory experiments (Choi et al 2016).…”
Section: Dynamics Of Debris-slit Dam Interactionmentioning
confidence: 63%
See 1 more Smart Citation
“…For clumps, the grain diameter is calculated as the equivalent diameter of a sphere with the same volume as the clump 5, it is worth noting that as b/d max increases from 3 to 7; more granular materials can pass through the slits. The evolutions of granular flow run up, pile up, and dead zone formation have also been observed in laboratory experiments (Choi et al 2016).…”
Section: Dynamics Of Debris-slit Dam Interactionmentioning
confidence: 63%
“…This approach may significantly reduce the destructive power of granular flow and thus the possibility of dam failure (Goodwin and Choi 2020). The performance of slit dam is influenced primarily by the so-called relative post spacing (Choi et al 2016), which is defined as the ratio of the post spacing (b) of the dam to the maximum particle diameter (d max ) of the debris materials. Ikeya and Uehara (1980) studied the response of different open-type dams and concluded that the slit dam could be blocked when b/d max is less than 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…In previous study, velocity attenuation is regarded as one of the significant functions of debris flow barriers (Choi, 2016). Moreover, the impact force is proportional to the velocity of debris flow (Hübl and Holzinger 2003;Scheidl et al 2013;He et al 2016).…”
Section: Velocity Attenuationmentioning
confidence: 99%
“…However, the aforementioned studies adopt monodisperse dry granular or pure water flows for studying the run-up mechanisms, without investigating the influence of particle size itself. Explicit consideration of particle size effect is important as it influences the energy attenuation during impact (Ashwood & Hungr, 2016;Koo et al, 2016;Choi et al, 2016a). have adopted three types of natural granular materials to study the effects of dynamic internal friction angle and particle diameter on the impact process.…”
Section: Introductionmentioning
confidence: 99%
“…Results demonstrate that particle characteristics have profound effects on the impact force. Choi et al (2016a) have investigated the influence of flows with different particle sizes impacting slit structures using glass spheres, demonstrating that large grains resulted in significant saltation, implying that the particle size is an important parameter to consider for flow-structure interaction. Two commonly adopted approaches for predicting run-up have been proposed by Jóhannesson et al (2009) and Kwan (2012).…”
Section: Introductionmentioning
confidence: 99%